The influence of flashcards on reading skills in early childhood - Dwi Arta, Sipa; Anggraeni, Ira (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2025)
This study aims to evaluate the effect of using flashcards on early reading skills of young children, while considering the potential drawbacks of overuse. The background acknowledges that although flashcards are effective for letter recognition and pronunciation, repetitive usage may cause learners’ boredom—flashcards may serve as a solution to learning fatigue, yet variation remains essential (digilib.uinkhas.ac.id). This Classroom Action Research (CAR) was conducted over two cycles—planning, implementation, observation, and reflection—with 15 group B children in early childhood education. Results showed improvement in reading abilities—letter recognition, sound pronunciation, and simple syllable formation. However, the findings also emphasize the importance of integrating other media, such as Augmented Reality, to maintain engagement and prevent monotony (edukatif.org). Therefore, while flashcards are an effective and engaging learning tool, their usage should be accompanied by creative variation to sustain effectiveness and learner interest.